Program Konservasi Mangrove di Pantai Glagah Wangi Demak Ditinjau dari Upaya Mencapai Sustainable Development Goals (SDGs) - Qo'im Rohmawati; Nanik Esti Wulandari; Ahmad Soleh; Rezki Widarti; Musyafiatun Musyafiatun; Grisselda Vania Putri; Fauzan Fauzan (Jurnal Kualita Pendidikan, 2022)
On the north coast of Central Java, the abrasion area has reached 5,500 hectares spread over 10 regencies/cities. Abrasion is the erosion or reduction of land (beach) due to wave activity, currents and tides. In Tambakbulusan Village, Karangtengah Subdistrict, Demak Regency, there is a Glagahwangi beach which is affected by abrasion. This study uses an interview approach, observation, and documentation techniques, which then support data obtained from research journals, online media, and others. Based on these problems, a mangrove conservation program was carried out on the Glagahwangi beach in an effort to achieve the SDGs in the pillars of environmental development which is a national program launched by the government. With this program, it is hoped that the preservation of the surrounding environment will improve, the welfare and economy of the surrounding community will increase. The results show that the mangrove conservation program has a tremendous positive impact on the environment, society, and the economy around the coast. In terms of the environment, mangrove conservation can protect biodiversity, namely aquatic semi-terrestrial and terrestrial, the life of future generations, clean water salinity, absorb pollutants, reduce the greenhouse effect with the "sequestration" mechanism, reduce CO2 in the atmosphere, and as the lungs of the world. . From an economic point of view, mangrove trees provide high economic value because parts of the mangrove tree can be processed and consumed, thus providing extraordinary benefits to the surrounding community in improving welfare. In addition, mangrove conservation can be used as an ecotourism area that aims to educate and preserve the environment and improve the economy of the community around the coast.